Bobot, Indeks Kuning Telur (IKT), Dan Haugh Unit (Hu) Telur Ayam Ras Setelah Perlakuan Dengan Pembungkusan Pasta Rimpang Temulawak (Curcuma xanthorrhiza Roxb). - Putri, Dyah Ayu Maharani; Djaelani, Muhammad Anwar; Mardiati, Siti Muflichatun (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Eggs are farm products that provide the greatest contribution to the achievement of community nutritional adequacy. The aims of the research was to an analyzed the quality of eggs in treatment without and with a temulawak rhizome pasta stored at 6,12, and 24 days. This research used 35 eggs consists of 7 treatment and 5 replication, namely PtT0 : as control, a group of eggs without packing temulawak rhizome pasta and without storage, PtT6 : a group of eggs without packing temulawak rhizome pasta after 6 days storage, PdT6 : a group of eggs with packing temulawak rhizome pasta after 6 days storage, PtT12 : a group of eggs without packing temulawak rhizome pasta after 12 days storage, PdT12 : a group of eggs with packing temulawak rhizome pasta after 12 days storage, PtT24 : a group of eggs without packing temulawak rhizome pasta after 24 days storage, and PdT24 : a group of eggs with packing temulawak rhizome pasta after 24 days storage. This research was analyzed used a completely randomized design (CRD). Variables measured were egg weight, yolk indeks, and Haugh Unit (HU). Data obtained from this study were analyzed using analysis of variance (ANOVA) if there is a real difference then continued further test using Duncan test at the level 95 %. The result egg weight reducted and yolk index shows was significantly different in PtT6, PtT12, PtT24, and PdT24 and Haugh Unit (HU) shows was significantly different in PtT6, PtT12, PtT24. Conclusion of this research is gived temulawak rhizome pasta are able to maintain the quality of eggs were observed on days 6, 12, and 24. Key Word : Chicken egg, Temulawak rhizome, Egg quality